2021
DOI: 10.17221/125/2020-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of site conditions on the properties of hawthorn (Crataegus azarolus L.) wood

Abstract: This study investigated the influence of site conditions on the physical and morphological properties of hawthorn (Crataegus azarolus L.) wood grown in Zagros forests of Iran. Hawthorn is a valuable woody species in Iran’s Zagros forests with data deficiency in its wood properties. To our best knowledge, there is no study on the properties of hawthorn wood. Twenty-seven mature trees were randomly chosen and sampled at three altitude levels (1 800–2 000, 2 000–2 200, and 2 200–2 400 m) in the Bazoft region of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The values of oven-dry density and basic density obtained in this study for the three species of almond were lower than those of other hardwoods, such as Persian oak and hawthorn growing in the Zagros forests, as reported by Bahmani et al (2018) and Nazari et al (2021). From the ANOVA test, there is a significant difference between wood species and volumetric shrinkage and volumetric swelling.…”
Section: Physical Properties Fizikalne Lastnostisupporting
confidence: 51%
See 1 more Smart Citation
“…The values of oven-dry density and basic density obtained in this study for the three species of almond were lower than those of other hardwoods, such as Persian oak and hawthorn growing in the Zagros forests, as reported by Bahmani et al (2018) and Nazari et al (2021). From the ANOVA test, there is a significant difference between wood species and volumetric shrinkage and volumetric swelling.…”
Section: Physical Properties Fizikalne Lastnostisupporting
confidence: 51%
“…Nazari et al (2020) studied the geographic variations of wood density and fibre dimensions of Persian oak wood, and reported a significant statistical effect of altitude and slope on the volumetric swelling of this material. In another study by Nazari et al (2021), the influence of site conditions on the physical and morphological properties of hawthorn (Crataegus azarolus) wood grown in the Zagros forests of Iran was investigated. They reported that there were statistically significant differences in the oven-dry density of hawthorn wood at various altitudes, while no significant differences were found between the values of volumetric shrinkage.…”
Section: Introduction Uvodmentioning
confidence: 99%
“…Finally, 2-4 rows of cells, immediately adjacent to the tree ring boundary and often pinching out, were commonly observed. Unfortunately, there is a lack of dendrochronological studies (this applies to all hawthorn species), although a few studies include comments on the age of trees, rings and growth rate [27,[42][43][44][45][46]. Of the approximately 50…”
Section: Discussionmentioning
confidence: 99%
“…Zagros forest in western Iran covers more than five million ha (Nazari et al 2021). This forests consists sub-Mediterranean, semiarid temperate climate, mainly consisting of deciduous, broad-leaved trees (Olfat and Pourtahmasi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that climate and environmental factors affect the quality of wood (Zobel andvan Buijtenen 1989, Nazari et al 2020). Climatic factors (temperature and rainfall), geographic features (latitude, elevation, and slope), biotic factors (animals, plants, humans, fungi, bacteria), and physical and chemical properties of soil can impact wood properties (Topaloglu et al 2016, Nazari et al 2021. Although numerous studies investigated the relationships between ecological indexes and wood properties (Rossi 2015, Topaloglu et al 2016, Sousa et al 2018, our knowledge is still limited regarding the relation between soil properties and variations in wood quality.…”
Section: Introductionmentioning
confidence: 99%